RANCANG BANGUN SISTEM DETEKSI POLA FRINJI UNTUK INTERFEROMETER MICHELSON - Eka Buanti; Minarni '; Walfred Tambunan (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Instrument used to precisely measure the wavelength of a laser light is known as a wavemeter. One of very important wavemeter parts is a fringe counting circuit. In this research a fringe counting circuit has been built and characterized using a Michelson Interferometer. The circuit system contained three parts i.e a current to voltage converter circuit for a photodiode, a TTL converter circuit, and a counting circuit. The circuits were characterized using two He-Ne laser with two different laser powers 1 mW and 5 mW which were used as the light source for a Pasco Michelson Interferometer. Two photodiodes with two different sensitive areas 100 mm2 and 7.5 mm2 were used. The research results showed that 1 mW Pudak He Ne laser resulted 2 µA for dark fringe and 8 µA for bright fringe when using 7.5 mm2 photodiode active area, then 3 µA for dark fringe and 400 µA for bright fringe when using 100 mm2 photodiode. The results for Meredith He Ne laser resulted 2 µA for dark fringe and 14 µA for bright fringe when using 7.5 mm2 photodiode, then 50 µA for dark fringe and 8000 µA for bright fringe when using 100 mm2 photodiode. The I toV converter which was designed produced voltage bigger than 5 V when using 100 mm2 photodiode. The counter circuit resulted 3.2 V TTL signal output for 200 mV TTL signal input with the same frequency.